Diplomatic Counterinsurgency : Lessons from Bosnia and Herzegovina. - Leroux-Martin, Philippe (Cambridge University Press, 2014)
This book provides an eyewitness account of a key political crisis triggered by the international community in Bosnia and Herzegovina in 2007.